Prevalence of Malnutrition in Various Political, Economic, and Geographic Settings. (February 2015) - Klek, Stanislaw; Krznaric, Zeljko; Gundogdu, Riza Haldun; Chourdakis, Michael; Kekstas, Gintautas; Jakobson, Triin; Paluszkiewicz, Piotr; Vranesic Bender, Darija; Uyar, Mehmet; Demirag, Kubilay; Poulia, Kalliopi Anna; Klimasauskas, Andrius; et al.
Background: Disease-related malnutrition (DRM) represents a critical public health concern. Therefore, Fight Against Malnutrition (FAM) should be a state priority, but the degree to which this is true appears to differ considerably among European countries. The aim of this study was to put the problem into perspective by comparing the prevalence of malnutrition in countries from opposite parts of the continent. Methods: Six countries—Croatia, Estonia, Greece, Lithuania, Poland, and Turkey—participated in the study. A short questionnaire was used to assess DRM: its prevalence, the current situation in hospitals, regulations for reimbursement, and general healthcare circumstances. Data from ESPEN's NutritionDay 2006 were used to broaden the perspective. Results: At admission in October 2012, 4068 patients were assessed. The study was performed in 160 hospitals and 225 units with 9143 beds. The highest proportions of patients with 3 or more points on the Nutritional Risk Screening 2002 were observed in Estonia (80.4%) and Turkey (39.4%), whereas the lowest were in Lithuania (14.2%). The provision of nutrition support was best in Turkey (39.4% required intervention, 34.4% received intervention) and Poland (21.9% and 27.8%, respectively). Nutrition support teams (NSTs) are active in some countries, whereas in others they virtually do not exist. Conclusion: The prevalence of malnutrition was quite high in some countries, and the nutrition approach differed among them. It could be the result of the lack of reimbursement, inactive or nonexistent NSTs, and low nutrition awareness. Those facts confirmed that the continuation of FAM activities is necessary.